Spontaneous Heterotopic Pregnancy: Diagnosis and Management - Katie P. Nguyen; Marlekah Hudspeth; Honey Milestone (Hindawi Limited, 2022)
Background. Heterotopic pregnancies albeit rare are conceivably life-threatening if missed. With the development of assisted reproductive techniques, the incidence has increased. Confirmation of an intrauterine pregnancy (IUP) should not preclude the existence of a heterotopic pregnancy. Case. A healthy 27-year-old patient (gravida 4, term 1, preterm 0, abortion 2, living 1) at approximately 5 weeks gestation through natural conception presented to the emergency room with acute abdominal pain and vaginal bleeding. Pelvic ultrasound showed evidence of an IUP and a right adnexal mass, raising suspicion for a heterotopic pregnancy. The patient underwent an uncomplicated laparoscopic right salpingectomy. An IUP was confirmed on ultrasound postoperatively. The patient had an early pregnancy loss at 8 weeks of gestation. Conclusion. With a high index of suspicion from clinical presentation and pelvic imaging, heterotopic pregnancy, while rare, should not be ruled out.